A systems-centered approach to inpatient group psychotherapy - Agazarian, Yvonne (Jessica Kingsley Publishers, 2001)
Annotation Systems-centered therapy is theory driven, therefore every intervention is in fact an hypothesis. This book is built around the transcript of an inpatient therapy session, giving the reader the opportunity to follow verbatim how systems-centered therapy actually works. The script tracks the initial techniques that introduce system-centered norms to a group.